Pertanggungjawaban Pidana Korporasi pada BUMN: Kasus Korupsi Penjualan Komoditas di Perum Bulog Jakarta (2022–2023) - Muzakki Ayatulloh GH; Nur’ainy Agmilya Sasmitha; Rahayu Sri Utami (Pemuliaan Keadilan, 2026)
This study discusses the function of corporate criminal liability for State-Owned Enterprises (SOEs), particularly SOEs, by examining a case of corruption in the sale of commodities at Perum Bulog Jakarta in 2022-2023, which caused financial losses to the state amounting to approximately IDR 7.192 billion. This case illustrates the abuse of authority by SOE officials, which not only reflects individual violations but also is a symptom of weaknesses in the culture of internal control and compliance in state-owned companies. The purpose of this study is to examine the regulation and application of the principle of corporate criminal liability in State-Owned Enterprises (SOEs) with reference to Law Law Number 31 of 1999 in conjunction with Law Number 20 of 2001 concerning Eradication of Corruption Crimes, the latest Criminal Code (Law Number 1 of 2023), and Supreme Court Regulation Number 13 of 2016. The method used is normative legal research with a juridical approach, which focuses on the review of legislation, the concept of corporate criminal liability, and the analysis of related court decisions. The results of the study show that acts of corruption involving Bulog have fulfilled the elements of corporate criminal liability, because they were carried out in the exercise of official authority and were intended for the benefit of the institution. The application of the provisions in the new Criminal Code, particularly Articles 45 to 47 and Article 118, confirms the position of corporations as legal subjects in the criminal law system. The implications of this research highlight the need to strengthen the Good Corporate Governance (GCG) system in SOEs and the need for consistent enforcement of corporate criminal liability by law enforcement officials to ensure justice, transparency, and the prevention of structural corruption in Indonesia.